Patterns of Constitutive and Inducible Clindamycin Resistance in Staphylococcus aureus Isolated from Clinical Samples by D-test Method, Shiraz, Southwest of Iran: - Seddigh Ebrahim Sarai, Hadi; Motamedifar, Mohammad; Mansury, Davood (Galen Medical Journal, 2014)
Background: Macrolides, Lincosamides and type B Streptogramins (MLSB) are commonly used for the treatment of Staphylococcal infections. Inducible MLSB resistance (iMLSB) cannot be identified by standard methods of antibiotic susceptibility testing. D-test appears to be a reliable indicator of iMLSB strains. The aim of this study was to determine the prevalence of Clindamycin resistance phenotypes in Staphylococcus aureus (S.aureus) isolated from clinical samples in Shiraz, southwest of Iran.Materials and Methods: This cross-sectional study was performed on a total of 302 S. aureus isolates which were collected from two teaching hospitals in Shiraz during 2012. Methicillin resistant Staphylococcus aureus (MRSA) were screened based on their resistance to 30Î¼g Cefoxitin disk. 168 Methicillin-sensitive Staphylococcus aureus (MSSA) and 134 MRSA isolates were tested in this study. The isolates were tested for susceptibility to Clindamycin (2 Âµg) and Erythromycin (15 Âµg) by Clinical and Laboratory Standards Institute (CLSI) recommended disk diffusion test.Results: Of 302 collected S. aureus isolates, 134 (44.4%) were MRSA and 168 (55.6%) were MSSA. Inducible MLSB resistance was observed in 10.4% of all recovered MRSA and 3% of all MSSA isolates. The majority of MRSA isolates (77.6%) constituted MLSB phenotype (cMLSB); this phenotype was seen in 4.1% of our tested MSSA isolates. Finally, 12.0% of MRSA isolates and 89.9% of MSSA showed sensitivity to both Erythromycin and Clindamycin.Conclusion: Different resistance patterns in hospitals indicated that performing routine D-test for S. aureus infections is highly recommended for each medical center. [GMJ. 2014;3(4):216-21]